2020
DOI: 10.1002/jgc4.1214
|View full text |Cite
|
Sign up to set email alerts
|

Consanguineous marriage and its effect on reproductive behavior and uptake of prenatal screening

Abstract: Consanguineous marriage is described as the union between a man and woman who share at least one common ancestor (Bittles & Black, 2010b). Consanguineous unions are common in many parts of the world. While it has declined in Western societies, consanguineous marriage is still common in North Africa, Middle East, and western Asia. Of all marriages in Turkey, 23% of them are consanguineous while rates around the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…This might be due to their fears of hereditary diseases or abortion as confirmed by many evidences. Indeed, previous studies found a double incidence of abortion cases among consanguineous marriage cases in Iraq (6), Turkey, 58 Azerbaijan, [59][60][61] and Egypt. 62 Overall, this is the first study on consanguinity conducted in Palestine recently.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to their fears of hereditary diseases or abortion as confirmed by many evidences. Indeed, previous studies found a double incidence of abortion cases among consanguineous marriage cases in Iraq (6), Turkey, 58 Azerbaijan, [59][60][61] and Egypt. 62 Overall, this is the first study on consanguinity conducted in Palestine recently.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, a study revealed that, the consanguineous couples were younger at the time of their marriages than non-consanguineous couples. The educational levels of both spouses in consanguineous marriages were lower than those in non-consanguineous marriages (Sahin et al, 2020). On the other hand, it was documented that CMs were more prevalent amongst young and uneducated women, living in rural areas, with poorer wealth status and having less exposure to mass media to access information (Iqbal et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…evlilikleri birçok sorunu beraberinde getiren ve özellikle gelişmekte olan ülkelerde ve düşük sosyo-demografik özelliklere sahip olan bölgelerde önemli bir sorundur. 24 Çalışmamızda akraba evliliği yapmayan kadınların değer biçme/değerlendirme düzeyleri daha yüksek bulunmuştur. Literatürde sağlık okuryazarlığı ile akraba evliliği değişkenlerini inceleyen çalışma sayısı çok kısıtlıdır.…”
Section: Akrabaunclassified